Model hipotetik pendidikan IPS berbasis pesantren untuk membangun kecerdasan sosial - Sholeh, Muh.; Affandi, Idrus; Komalasari, Kokom; Wiyanarti, Erlina (Universitas Negeri Yogyakarta, 2023)
The purpose of this research is to analyze the social studies value-based hypothetical model of Islamic boarding schools to build social intelligence. This research was conducted at the Islamic Boarding School of Al-Ihya 'Ulumaddin Cilacap Indonesia using a qualitative approach with the case study method. The data were obtained through observation of educational activities in Islamic boarding schools, in-depth interviews with informants, and evaluation of the documents obtained during the research process. The data is then analyzed through reduction, presentation, and conclusion/verification. Based on these stages, it is then presented in the form of information about a hypothetical model of social studies education based on Islamic boarding schools. Values education in Islamic boarding schools is carried out integrally in a religious education system that refers to several sources, namely Islamic religious teachings, the legacy of the clergy, the heritage of Islamic boarding schools, the thoughts of Imam Ghozali, the thoughts of the founders of the Islamic boarding school, community culture, and Pancasila. The values explored and developed at Islamic boarding schools consist of worship values, suhbah values, taadun values, tawasuth values, consistent commitment values, istiqomah values, patience and gratitude values, taawun values, mutual respect values, perseverance values, simplicity values, values courage over kindness, and the value of sincerity. The hypothetical model of social studies education based on Islamic values is carried out by bringing students to the pesantren environment to be involved in learning activities so that students can feel the atmosphere of the Islamic boarding school environment. The key to the success of values education in Islamic boarding schools is leadership and exemplary kyai so that support from all components appears, both from the internal pesantren and the community. Keywords: Hypothetical Model, Social Studies Education, Islamic Boarding School Values